การสังเคราะห์และการประเมินฤทธิ์ต้านอักเสบของเคอร์คิวมินโปรดรักส์ - นพสิทธิ์ มุสิวีรพัฒน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
Curcumin, a polyphenolic compound found in turmeric (Curcuma longa L.), has been shownfor its potential in the treatment of human diseases. However, the development of curcurnin for clinical applications is hindered from its low water solubility (~0.068 μg/m). In this study, we aimed to synthesize curcumin monoglutaric acid (CMG) as a new curcumin prodrug and to compare the water solubility and anti-inflammatory activity with curcumin. The synthesis of CMG was achieved by glutarylating a phenolic hydroxyl group of curcumin with glutaric anhydride using 4-dimethylaminopyridine as a catalyst. The reaction yield was 46.5%. The synthesized CMG was then structurally characterized by nuclear magnetic resonance spectroscopy and liquid chromatography-quadrupole time-of-flight mass spectrometry. The water solubility of CMG was determined in accordance with the OECD guideline using high-performance liquid chromatography. The water solubility of CMG at 25.0±0.1͒ Cwas 8.06±0.61 μg/ml. Anti-inflammatory effects of CMG and curcumin were evaluated at 5uM using interleukin-1β-induced human epithelial colorectal adenocarcinoma cell lines (IL-1β-induced Caco- 2 cell lines) as a cellular model Interleukin-8 (IL-8), prostaglandin E-2 (PGE-2) and cyclooxygenase-2 (COX-2) were used as inflammatory protein markers for the assay. The cells treated with 0.5% dimethyl sulfoxide were used as a control. The reduction of IL-8 and PGE-2 secreted by the IL- 1β-induced Caco-2 cells detected by ELISA was found to be 46.87 and 40.41%, respectively, for CMG and 25.08 and 23.71%, respectively, for curcumin. Western blot analysis also demonstrated that CMG and curcumin reduced COX-2 expression in the induced cells by 42.37 and 21.86%, respectively. Therefore, CMG is a prodrug of curcumin with improved water solubility and enhanced anti-inflammatory activity, and has the potential to be further investigated for the anti-inflammatory activity in animal models.